The Impact of an Educational Programme Based on the IDEAL Model on Reducing Cognitive Failure and the Acquisition of Certain Basic Basketball Skills - Ayad Ghani Jasim (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The aim of this study was to investigate the effect of an educational programme based on the IDEAL model on reducing cognitive failure and the acquisition of certain basic basketball skills among students. The researcher adopted an experimental approach due to its suitability for the nature of the research problem, using a two-group design with pre- and post-tests. The research population comprised first-year students at the Faculty of Physical Education and Sports Sciences, Samarra University, for the academic year (2025–2026). The research sample comprised 40 students, who were randomly divided into two equivalent groups: 20 students in the experimental group, who underwent an educational programme based on the IDEAL model, and 20 students in the control group, who followed the curriculum taught by the subject teacher. The researcher employed the Cognitive Failure Scale, as well as a number of basketball skill tests, namely: chest dribbling, dribbling between cones, lay-ups and free throws, to measure the level of mastery of basic skills among the sample participants. The researcher concluded that the educational programme based on the IDEAL model contributed positively to reducing cognitive failure and improving the learning of certain basic basketball skills, and recommended the adoption of modern educational models based on thinking and problem-solving in physical education lessons, given their active role in developing students’ cognitive and skill-based abilities.